Deductive‐reasoning brain networks: A coordinate‐based meta‐analysis of the neural signatures in deductive reasoning. Issue 12 (29th September 2020) - Wang, Li; Zhang, Meng; Zou, Feng; Wu, Xin; Wang, Yufeng
Abstract: Objective: Deductive reasoning is a complex and poorly understood concept in the field of psychology. Many cognitive neuroscience studies have been published on deductive reasoning but have yielded inconsistent findings. Methods: In this study, we analyzed collected data from 38 articles using a recently proposed activation likelihood estimation (ALE) approach and used conjunction analysis to better determine the intersection of the results of meta‐analyses. Results: First, the left hemispheres in the inferior parietal lobule (Brodmann area 40 [BA40]), middle frontal gyrus (BA6), medial frontal gyrus (BA8), inferior frontal gyrus (BA45/46), caudate, and insula (BA47) were revealed to be significant brain regions via simple‐effect analysis (deductive reasoning versus baseline). Furthermore, IFG, insula, and cingulate (the key neural hubs of the cingulo‐opercular network) were highlighted in overlapped functional connectivity maps. Conclusion: The findings of the current study are consistent with the view that deductive reasoning requires a succession of stages, which included decoding of linguistic information, conversion and correction of rules, and transformation of inferential results into conclusive outputs, all of which are putatively processed via a distributed network of brain regions encompassing frontal/parietal cortices, as well as the caudate and other subcortical structures, which suggested that in the process of deductive reasoning, the coding and integration of premise information is indispensable, and it is also crucial to the execution and monitoring of the cognitive processing of reasoning. Abstract : Deductive reasoning is supported by a distributed network of regions encompassing frontal/parietal cortices and subcortical structures (e.g., caudate). The results of our conjunction analysis highlight the IFG, insula, and cingulate (the key neural hubs of the cingulo‐opercular network) as core locus of deductive reasoning.